E-Coklit: Voter Data Updating and Effectiveness - Elsya Rachma Andyas; Hery Nariyah; Raden Mahendra Haryo Bharoto (Riviera Publishing, 2024)
Elections are the main basis for running a democratic system, and updating voter data is an important aspect to ensure the integrity and validity of the process. As a new innovation by the KPU (General Election Commissions) that utilizes information technology, namely E-Government, it is therefore necessary to analyze the effectiveness of using the E-Coklit application. Based on Budiani's theory of effectiveness, this research uses four main variables: accuracy of program targets, program socialization, program objectives, and program monitoring. The research method used was descriptive qualitative with interviews and observations as well as documentation from the agency as data collection techniques. The results showed that the E-Coklit application made it easier for Pantarlih (Voter Data Update Officer) to carry out voter data matching and research activities, with the results of more valid data accuracy and a centralized data system. The use of the E-Coklit application in Majalengka District has shown good results, but requires further improvement to achieve maximum effectiveness.